Do Microbiota in the Soil Affect Embryonic Development and Immunocompetence in Hatchling Reptiles? - Brown, Gregory P.; Shine, Richard (Frontiers in Ecology and Evolution, 2022)
Reptile eggs develop in intimate association with microbiota (bacteria, viruses, etc.) in the soil, raising the possibility that embryogenesis may be affected by shifts in soil microbiota caused by anthropogenic disturbance, translocation of eggs for conservation purposes, or laboratory incubation in sterile media. To test this idea we incubated eggs of keelback snakes (Tropidonophis mairii, Colubridae) in untreated versus autoclaved soil, and by injecting lipopolysaccharide (LPS) into the egg to induce an immune response in the embryo. Neither treatment modified hatching success, water uptake, incubation period, or white-blood-cell profiles, but both treatments affected hatchling size. Eggs incubated on autoclaved soil produced smaller hatchlings than did eggs on untreated soil, suggesting that heat and/or pressure treatment decrease the soil’s suitability for incubation. Injection of LPS reduced hatchling size, suggesting that the presence of pathogen cues disrupts embryogenesis, possibly by initiating immune reactions unassociated with white-blood-cell profiles. Smaller neonates had higher ratios of heterophils to leucocytes, consistent with higher stress in smaller snakes, or body-size effects on investment into different types of immune cells. Microbiota in the incubation medium thus can affect viability-relevant phenotypic traits of hatchling reptiles. We need further studies to explore the complex mechanisms and impacts of environmental conditions on reptilian embryogenesis.